Experience of adherence to treatment among patients with coronary artery disease during the COVID-19 pandemic: A qualitative study - Nasrin Zahmatkeshan; Zahra Khademian; Ladan Zarshenas; Mahnaz Rakhshan (Tabriz University of Medical Sciences, 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic has caused patients with chronic diseases to face various challenges. The present qualitative study aimed to explore adherence to treatment in patients with coronary artery disease (CAD) during the COVID-19 pandemic. Methods: This qualitative content analysis was conducted from September 2020 to February 2021. Online in-depth interviews were conducted with 15 patients with CAD after discharge from Nemazi and Al-Zahra heart hospitals, Shiraz, Iran. Data management was done via MAXQDA 12 software using conventional content analysis based on the method proposed by Graneheim and Lundman. Results: The results revealed three main categories, nine subcategories, and 431 primary codes. The first category was 'improved self-care in the shadow of COVID-19' (Improving self-care due to fear of COVID-19, 'utilization of alternative strategies, and reinforcement of self-care beliefs). The second category was 'redefinition of support systems' (need for a support system, seeking for alternative support systems, and changes in social interactions). The last category was 'barriers to treatment adherence' (shortage of financial resources, need to adjust with working conditions, and mental conflicts). Conclusion: The results indicated that the COVID-19 threats encouraged the patients with CAD to adhere to their care principles. Nonetheless, the restrictions resulting from the pandemic caused problems in adherence to treatment. Thus, redefinition of the support systems in accordance with the present conditions are recommended.